Biochemical and Phylogenetic Characterization of a Novel NADP+-Specific Isocitrate Dehydrogenase From the Marine Microalga Phaeodactylum tricornutum - Huang, Shiping; Zhao, Jiaxin; Li, Wenjing; Wang, Peng; Xue, Zhenglian; Zhu, Guoping (Frontiers in Molecular Biosciences, 2021)
Isocitrate dehydrogenase (IDH) family of proteins is classified into three subfamilies, namely, types I, II, and III. Although IDHs are widely distributed in bacteria, archaea, and eukaryotes, all type III IDHs reported to date are found only in prokaryotes. Herein, a novel type III IDH subfamily member from the marine microalga Phaeodactylum tricornutum (PtIDH2) was overexpressed, purified, and characterized in detail for the first time. Relatively few eukaryotic genomes encode this type of IDH and PtIDH2 shares the highest homology with marine bacterial monomeric IDHs, suggesting that PtIDH2 originated through a horizontal gene transfer event between a marine alga and a bacterium. Size-exclusion chromatography revealed that the native PtIDH2 is a homotetramer (~320 kDa) in solution, comprising four monomeric IDH-like subunits (80 kDa each). Enzymatic characterization showed that PtIDH2 is a bivalent metal ion-dependent enzyme and Mn2+ is the optimal activator. The recombinant PtIDH2 protein exhibited maximal activity at 35 ℃ and pH 8.0 in the presence of Mn2+. Heat-inactivation analysis revealed that PtIDH2 is a cold-adapted enzyme. Kinetic analysis demonstrated that PtIDH2 is a completely NADP+-specific IDH with no detectable NAD+-associated catalytic activity. The three putative key NADP+-binding residues (His604, Arg615, and Arg664) in PtIDH2 were also evaluated by site-directed mutagenesis. The H604L/R615D/R664S triple mutant showed a 3.25-fold preference for NAD+ over NADP+, implying that the coenzyme specificity of PtIDH2 can be converted from NADP+ to NAD+ through rational engineering approaches. Additionally, the roles of the conserved residues Ala718 and Leu742 in the thermostability of PtIDH2 were also explored by site-directed mutagenesis. We found that the L742F mutant displayed higher thermostability than wild-type PtIDH2. This study expands the phylogeny of the IDH family and provides new insights into the evolution of IDHs.